Pulpal dressing condensation methods in pulpotomy for primary molars: An in-vitro comparative study - Tarun Walia; Wed Fahmi Ali Alzayer; Mohammed Nemer A. Al Nemer (Elsevier, 2021)
Purpose: To compare three condensation techniques of zinc oxide eugenol (ZOE) as a pulpal dressing material during pulpotomy in extracted primary molars. Material and Methods: Sixty primary first and second molars were embedded in individual wax casts and divided into three groups consisting of 20 teeth each. In group I, the ZOE base was condensed by an amalgam condenser, while a moist cotton pellet was used in group II. A combination of an amalgam condenser and a wet cotton pellet tested the condensation mentod in group III. The condensation quality of the three techniques was evaluated through two digital periapical radiographs taken in a lateral and anterior-posterior direction. Results: Non-parametric Kruskal-Wallis test showed that there was no significant difference between the technique and quality of ZOE compaction. However, a significant difference was observed on condensation assessment for combined three groups on lateral radiographs vs the appearance on antero-posterior radiographs with the p-value set at < 0.05. Conclusion: Voids appeared with all three techniques. A combination of an amalgam condenser and the wet cotton wool pellet was the least effective method of condensation. Lateral radiographs revealed much fewer spaces between the ZOE and pulpal floor in comparison to antero-posterior images.